Egypt 2015 : perspectives of research : proceedings of the Seventh European Conference of Egyptologists : 2nd-7th June 2015, Zagreb, Croatia - Tomorad, Mladen,; Popielska-Grzybowska, Joanna, (Archaeopress Egyptology ;, 2017)
The Seventh Central European Conference of Egyptologists. Egypt 2015: Perspectives of Research (CECE7) was held at the University of Zagreb in Croatia in 2015. It was co-organised by two scholarly institutions: the Department of History at the Centre for Croatian Studies of the University of Zagreb, Croatia (Dr Mladen Tomorad), and the Department of Ancient Cultures of the Pultusk Academy of Humanities in Pultusk, Poland (Dr Joanna Popielska-Grzybowska). This book presents a selection of papers which were read at the conference. The volume is divided into six sections in which thirty-two scholars from fourteen European countries cover various fields of modern Egyptological research.